Mechanism of oxygen atom transfer from Fe-V(O) to olefins at room temperature - Singh, Kundan K.; Tiwari, Mrityunjay K.; Dhar, Basab B.; Vanka, Kumar; Sen Gupta, Sayam (Inorganic Chemistry, 2015)
In biological oxidations, the intermediate Fe-V(0)(OH) has been proposed to be the active species for catalyzing the epoxidation of alkenes by nonheme iron complexes. However, no study has been reported yet that elucidates the mechanism of direct O-atom transfer during the reaction of Fe-V(0) with alkenes to form the corresponding epoxide. For the first time, we study the mechanism of O-atom transfer to alkenes using the Fe-V(0) complex of biuret-modified Fe-TAML at room temperature. The second-order rate constant (k(2)) for the reaction of different alkenes with Fe-V(0) was determined under single-turnover conditions. An 8000-fold rate difference was found between electron-rich (4-methoxystyrene; k(2) = 216 M-1 s(-1)) and electron-deficient (methyl transcinnamate; k(2) = 0.03 M-1 s(-1)) substrates. This rate difference indicates the electrophilic character of Fe-V(0). The use of cis-stilbene as a mechanistic probe leads to the formation of both cis- and trans-stilbene epoxides (73:27). This suggests the formation of a radical intermediate, which would allow C-C bond rotation to yield both stereoisomers of stilbene-epoxide. Additionally, a Hammett rho value of -0.56 was obtained for the para-substituted styrene derivatives. Detailed DFT calculations show that the reaction proceeds via a two-step process through a doublet spin surface. Finally, using biuret-modified Fe-TAML as the catalyst and NaOCl as the oxidant under catalytic conditions epoxide was formed with modest yields and turnover numbers.

Unraveling origins of the heterogeneous curvature dependence of polypeptide interactions with carbon nanostructures - Jana, Asis K.; Tiwari, Mrityunjay K.; Vanka, Kumar; Sengupta, Neelanjana (Physical Chemistry Chemical Physics, 2016)
Emerging nanotechnology has rapidly broadened interfacial prospects of biological molecules with carbon nanomaterials (CNs). A prerequisite for effectively harnessing such hybrid materials is a multifaceted understanding of their complex interfacial interactions as functions of the physico-chemical characteristics and the surface topography of the individual components. In this article, we address the origins of the curvature dependence of polypeptide adsorption on CN surfaces (CNSs), a phenomenon bearing an acute influence upon the behavior and activity of CN-protein conjugates. Our benchmark molecular dynamics (MD) simulations with the amphiphilic full-length amyloid beta (A beta) peptide demonstrate that protein adsorption is strongest on the concave (inner) CN-surface, weakest on the convex (outer) surface, and intermediary on the planar surface, in agreement with recent experimental reports. The curvature effects, however, are found to manifest non-uniformly between the amino acid subtypes. To understand the underlying interplay of the chemical nature of the amino acids and surface topography of the CNs, we performed high-level quantum chemical (QM) calculations with amino acid analogs (MA) representing their five prominent classes, and convex, concave and planar CN fragments. Molecular electrostatic potential maps reveal pronounced curvature dependence in the mixing of electron densities, and a resulting variance in the stabilization of the non-covalentty bound molecular complexes. Interestingly, our study revealed that the interaction trends of the high-level QM calculations were captured well by the empirical force field. The findings in this study have important bearing upon the design of carbon based bio-nanomaterials, and additionally, provide valuable insights into the accuracy of various computational techniques for probing non-bonded interfacial interactions.

Unraveling the hidden role of the counteranion in ``cation in a cage'' systems - Mukherjee, Anagh; Ghule, Siddharth; Tiwari, Mrityunjay K.; Vanka, Kumar (Journal of Physical Chemistry A, 2020)
The current work showcases general principles at play in systems consisting of cations present inside molecular cages. Such systems, relevant to chemistry and biology, have been carefully investigated by computational methods. The important Ge(II)-encapsulating cage systems have been studied first. The very fact that such compounds exist appears highly unlikely, given the highly reactive nature of the Ge(II) dication. Our studies reveal what really occurs in solution when such complexes are formed: the Ge(II) dications are actually present as [Ge-X](+) (where X is the ``non-coordinating'' counterion employed in such systems) during entry and subsequent existence at the center of the cage. Hence, what is actually present is a ``pseudomonocation''. Interestingly, such pseudomonocation-encapsulated cages are seen to be equally relevant in systems of biological importance, such as for dicationic s block-based ionophores. In explaining such cases, the concept of ``isoionicity'' is introduced, demonstrating that the counterion-coordinated dications are isoionic with a monocation, such as Li(I), isolated in the same ionophore.

Size matters: computational insights into the crowning of noble gas trioxides - Dash, Soumya Ranjan; Sharma, Himanshu; Tiwari, Mrityunjay K.; Greb, Lutz; Vanka, Kumar (Inorganic Chemistry, 2024)
In pursuit of enhancing the stability of the highly explosive and shock-sensitive compound XeO3, we performed quantum chemical calculations to investigate its possible complexation with electron-rich crown ethers, including 9-crown-3, 12-crown-4, 15-crown-5, 18-crown-6, and 21-crown-7, as well as their thio analogues. Furthermore, we expanded our study to other noble gas trioxides (NgO(3)), namely, KrO3 and ArO3. The basis set superposition error (BSSE) corrected interaction energies for these adducts range from -13.0 kcal/mol to -48.2 kcal/mol, which is notably high for sigma-hole-mediated noncovalent interactions. The formation of these adducts was observed to be more favorable with the increase in the ring size of the crowns and less favorable while going from XeO3 to ArO3. A comprehensive analysis by various computational tools such as the mapping of the electrostatic potential (ESP), Wiberg bond indices (WBIs), Bader's theory of atoms-in-molecules (AIM), natural bond orbital (NBO) analysis, noncovalent interaction (NCI) plots, and energy decomposition analysis (EDA) revealed that the C-H center dot center dot center dot O interactions, as well as dispersion interactions, play a pivotal role in stabilizing adducts involving larger crowns. A noteworthy outcome of our study is the revelation of a coordination number of 9 for xenon in the complex formed between XeO3 and the thio analogue of 18-crown-6, which is higher than the largest number reported to date.

Ionic liquid driven Refined functionalization of graphene oxide: An insight via combined experiments and theory - Kewat, Heera Lal; Dutta, Debangkana; Ajithkumar, T. G.; Chavda, Dhruvil; Sharma, Rahul Kumar; Tiwari, Mrityunjay K.; Sidiqi, Ubaid; Manna, Moutusi; Nigam, Sandeep; Ghosh, Pushpal (Carbon, 2025)
Functionalizing graphene and its derivative, or doping them with heteroatoms can significantly enhance their optoelectronic, photonic and bio-photonic properties; but controlled and tuneable functionalization of GO is still in their infancy. Herein, a series of functionalized graphene oxide (FGO) are synthesized solvothermally by using task specific ionic liquids (ILs) of varying alkyl chain length; 1-alkyl-3-methylimidazolium tetra fluoroborate, [Cnmim]BF4 (n = 2, 4 etc.). ILs are not only used as a solvent but also as source of fluoride ion for functionalization of GO. A drastic decrease in the oxygen containing functional groups of GO upon fluorination is evidenced by FTIR, Raman, XPS, EDX analysis and electrochemical study. Solid state 19F NMR spectroscopy indicates that, fluorination happens exclusively in edge positions, not on basal planes. Band gap of FGOs decreases along with increasing the chain length of ILs. Further, intense blue emission and high photocatalytic efficiency, using crystal violet as model dye are observed for all the FGOs under visible light. The tailored functionalization by varying alkyl chain length of IL has been rationalized by DFT calculations. It has been realized that owing to the ease of dissociation for [Cnmim]BF4 complexes with n >= 10; greater extent of fluorination/functionalization of GO has been observed. Elimination of a non-covalent interaction on increasing the alkyl chain length has been attributed for lower stability of higher chain length IL which in turn renders ease of dissociation. Easy yet controlled functionalization of GO using tuneable ILs can open a new direction in the environment friendly synthesis and applications.
Keywords: fluorination; Functionalization; graphene oxide; ionic liquids; Luminescence; Photocatalysis